Recent advances in immunomodulation of reproduction - YADAV, M P; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2023)
Modulation of reproductive functions through immunological approach in livestock is fairly a recent development. Gonadal functions can be suppressed through the use of antifertility vaccin developed against reproductive hormones and gamete antigens (Sperm and zona pellucida of ovum). This concept has been utiliziecj for immunosterilization of animals. Ovulation rate and reproductive efficiency on the other hand. may be increased through the use offecundity vaccine. Immunization against inhibin has shown promising results for increasing ovulation rate and litter size. Immunomodulation of uterine defense is another area currently being under intensive investigation. Immunomodulators may be considered as an alternative therapeutic agent in clinical and subclinical uterine infections. Trophoblastic protein(s)or interferon purified recently in some oftl1e animal species has potential application in regulation offertility.